Differences in antimicrobial resistance gene abundance and microbial diversity of the gut microbiome in patients on antibiotics enrolled in a clinical trial - Adam G. Stewart; Patrick N. A. Harris; Rikki M. A. Graham; Amy V. Jennison; Sanmarie Schlebusch; Asha Kakkanat; Tiffany Harris-Brown; David L. Paterson; Brian M. Forde (Therapeutic Advances in Infectious Disease)
Background: Understanding how the gut microbiome adapts on exposure to individual antibiotics, with respect to antimicrobial resistance gene (ARG) enrichment, is important. Objectives: To characterise the changes that occur in the gut microbiome of patients enrolled in an antibiotic clinical trial and to propose methods in which to embed gut microbiome analysis into clinical trials. Design: This was a prospective cohort study of hospitalised patients who were successfully enrolled and randomised into two clinical trials between January 2021 to December 2021. Methods: Adult patients admitted to the hospital with a bloodstream infection have been randomised to receive either benzylpenicillin, ampicillin, cefazolin, ceftriaxone, piperacillin-tazobactam or meropenem at a single institution. Faecal specimens were collected at enrolment and every second day until discharge. Each specimen underwent DNA sequencing to determine microbial diversity and ARG abundance. Results: Ten patients (including six females) were included. DNA concentration and sampling quality were markedly lower for rectal swabs compared to stool samples. Relative abundance of Enterococcus faecium was increased in individual patients where treatment included ampicillin, meropenem and piperacillin-tazobactam. Piperacillin-tazobactam also increased the abundance of key beta-lactamase genes ( bla SHV-100 , bla OXA-392 , bla CMY-18 ). Ampicillin increased the abundance of bla TEM-1A . There were no extended-spectrum beta-lactamase (ESBL) or carbapenemase genes detected in our study. The presence of key anaerobes such as Clostridium and Bifidobacterium species appeared to play an important role in colonisation resistance of E. faecium and Clostridioides difficile . Conclusion: Differential changes in anaerobic bacterial genera on exposure to antibiotics may be a key determinant of colonisation resistance. The pre-analytical phase of microbiome analysis is a critical factor in data quality and interpretation.